Studi Potensi Kawasan Subak Sebagai Ekowisata di Desa Belimbing Kecamatan Pupuan Kabupaten Tabanan - INDRAYUNI, DEWA AYU BULAN; KOHDRATA, NANIEK; SUKEWIJAYA, I MADE (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016DO - 10.24843/JAL.2016.v02.i01.p10)
ABSTRACT Potential Study of Subak Area for Ecotourism in Belimbing Village, Pupuan District, Tabanan Regency Tabanan regency is the highest rice producing regency in Bali. The suvvess in agricultural production is inseparable from Subak organization existency. This past few years, Tabanan experiencing an increase land conversion. It becomes a threat to the existence of Subak. Developing ecotourism in Subak area is an effort to reduce numbers of land conversion and Subak degradation. Belimbing village has a potential to be developed as ecotourism. The potential identification in Subak area of the village shows there are some Subak values as well as environment potentials that can be developed as area for ecotourism. The beautiful landscape of rice field terrace, Tri Hita Karana (THK) based agricultural and local community social cultured activities are potential for tourist attraction. However, there is a need to educate the local people in order to support the implementation of ecotourism in Subak area of Belimbing village. By developing Subak area as ecotourism, it is expected to improve the welfare of the local people, especially former and Subak organization also preserve the environment as well. Keywords: ecotourism, identification of potential, subak areas